Mathematics at a Technical University: the Potential of Horizontal Connections - Tolkacheva, Elena (Computer Tools in Education, 2021)
Horizontal connections, which are implemented at the Department of Algorithmic Mathematics of St. Petersburg State Electrotechnical University «LETI» as an integral part of the methodology of the Procotech approach to learning, are described. From the statement of the goal of developing the thinking of a professional, in this case technical thinking, in the process of studying at a technical university, general psychophysiological issues of the formation and development of thinking during training arise. In modern technical education, competencies related to information and knowledge — their extraction, transformation and application — are increasingly relevant. Competencies of this kind imply not only the development of information skills, but also the flexibility of the subject’s mental activity, since it is human reasoning that becomes the ideal basic model for technology. Mathematics and other fundamental disciplines in technical universities are taught mainly in the first year of education. This forces us to plan not only the content of disciplines, but also training in methods of organizing mental work and preparation for increasing the intensity of mental work. Horizontal connections are shown as potential to activate the intellectual work of students, increase their academic motivation, as well as increase the stability mental activity system with an increase in workload.